EDUKASI LITERASI DIGITAL UNTUK MEMINIMALISIR PENYEBARAN HOAX DI KALANGAN PELAJAR - Putra, Robhans Vickidella Hartono; Maulani, Defani Bunga; Pebriyanti, Elsa Ayu; Septiani, Yesi Resina; Namira, Zahwa Salsa; Alifia, Saskia Putri; Pridasa, Nazwa Naysilla; Fitriani, Ai Asri; Ramdhani, Adrian; Aprilian, Ridho Muhammad Jihad; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The proliferation of hoaxes among students represents a significant challenge in the digital age, with the potential to impair their overall comprehension and critical thinking abilities. This article presents a review of community service activities designed to enhance students' digital literacy, with the objective of reducing the dissemination of hoaxes. The principal objective of this activity is to equip students with the capacity to distinguish between reliable and unreliable information and to enhance their awareness of the detrimental impact of hoaxes. The approach employed comprised interactive presentations and group discussions. This activity was implemented at SMP Negeri 17 Tasikmalaya. The results demonstrated a notable enhancement in students' comprehension of the concept of digital literacy and their capacity to discern misinformation. This activity is deemed efficacious in fostering students' critical abilities and curbing the potential for disseminating hoaxes within the school environment. This illustrates that the objectives of the service have been met.